PENERAPAN METODE INTERPOLASI LAGRANGE DALAM MEMPREDIKSI JUMLAH PENDUDUK PROVINSI NUSA TENGGARA TIMUR - Roberta Uron Hurit; Maria Yustina Nanga (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study aims to predict the population of the province of East Nusa Tenggara by applying the Interpolation method. The research method used is the method of literature study and computer programming simulation MATLAB and Exel. Data were obtained from the Central Statistics Agency (BPS) from 1971, 1980, 1990, 1995, 2000, and 2010. Knowledge of population development each year would be difficult to know if the population census was only conducted once every ten years. Therefore, an alternative mathematics that can be used as a reference for solving the problem of population size each year is numerical forecasting, namely the interpolation method. By using the Lagrange interpolation method, it is found that every year the population increases by an average of 2.107%. The solution expected from this research is the existence of government programs that can reduce the birth rate and reduce the number of transmigrants.